2019
DOI: 10.1088/1361-6463/ab1626
|View full text |Cite
|
Sign up to set email alerts
|

Study on the defect density of states in light soaking effect enhanced performance of perovskite solar cells

Abstract: The light soaking phenomenon, in chlorine-based mixed halide perovskite solar cells (PSC) with p-i-n configuration, is studied. Due to light soaking, the solar cells have shown improved open circuit voltage, fill factor (FF), and power conversion efficiency without much change in short circuit current. The devices have returned to their original state upon extended exposure to dark conditions. Capacitance spectroscopy is used to understand the effect of light soaking on various photovoltaic parameters. The obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…The high frequency range is the carrier freeze region. 52 As shown in Figure 7, at high frequency, the capacitance values are substantially coincident and do not change with illumination, indicating the intrinsic perovskite properties. There are also no major changes at the intermediate frequency range.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The high frequency range is the carrier freeze region. 52 As shown in Figure 7, at high frequency, the capacitance values are substantially coincident and do not change with illumination, indicating the intrinsic perovskite properties. There are also no major changes at the intermediate frequency range.…”
Section: Resultsmentioning
confidence: 78%
“…The C–f diagram is usually divided into 3 parts. , The low frequency region capacitance corresponds to the electron and possible ion accumulation process and involves the defect state at the interface between perovskite and contact layers. , The intermediate frequency capacitive response of the forming platform is related to the intrinsic dielectric polarization of perovskite. The high frequency range is the carrier freeze region . As shown in Figure , at high frequency, the capacitance values are substantially coincident and do not change with illumination, indicating the intrinsic perovskite properties.…”
Section: Resultsmentioning
confidence: 82%
“…This indicates that the LSE is somehow an intrinsic property of bulk LHPs. Using capacitance spectroscopy, Srivastava et al 27 showed that the defect density in PSC reduced from 10 16 to 10 15 cm −3 after light soaking, directly indicating that point defects are involved in LSE.…”
mentioning
confidence: 99%
“…Figure a is the capacitance–frequency graph (C–F). It shows three different regions such as (a) high frequency (HF), (b) midfrequency (MF), and low frequency (LF), where capacitance at low frequency is increasing with respect to light illumination as the surface is populated increasing with the charged species that resulted by the action of SS …”
Section: Alternating Current Techniques For Pc and Pec Interfacesmentioning
confidence: 99%